Carbon dioxide transfer over a Central Amazonian rain forest - Malhi, Yadvinder Singh; Nobre, Antônio Donato; Grace, John; Kruijt, Bart J.; Pereira, Maria G.P.; Culf, Alistair D.; Scott, Steve L. (Journal of Geophysical Research Atmospheres, 1998)
Tropical rain forests are among the most important and least monitored of terrestrial ecosystems. In recent years, their influence on atmospheric concentrations of carbon dioxide and water vapor has become the subject of much speculation. Here we present results from a yearlong study of CO2 fluxes at a tropical forest in central Amazonia, using the micrometeorological technique of eddy covariance. The diurnal cycle of CO2 flux was consistent with previous short-term studies in tropical rain forests, implying that the Amazonian rain forest shows a fair degree of spatial uniformity in bulk ecophysiological characteristics. Typical peak daytime photosynthesis rates were 24-28 μmol CO2 m-2 s-1, and respiration rates were 6-8 μmol CO2 m-2 s-1. There was significant seasonality in peak photosynthesis over the year, which appeared strongly correlated with soil moisture content. On the other hand, there was no evidence of strong seasonality in soil respiration. Central Amazonia has only a short, 3-month dry season, not atypical of tropical rain forest, and it is therefore likely that large areas of Amazonia exhibit significant seasonality in photosynthetic capacity. The gross primary production was calculated to be 30 t C ha-1 yr-1. An analysis of data quality is included in the appendix. Copyright 1998 by the American Geophysical Union.
Keywords: Boundary Layer; Carbon Dioxide; Gas Exchange; Rainforest; Tropical Forest; Amazonia; South America